2016
DOI: 10.1002/oby.21729
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on body composition and bone mineral density in breast cancer survivors taking aromatase inhibitors

Abstract: Objective We examined the effect of 12 months aerobic and resistance exercise vs. usual care on changes in body composition in postmenopausal breast cancer survivors taking aromatase inhibitors (AIs). Methods 121 breast cancer survivors were enrolled in the Hormones and Physical Exercise (HOPE) study and randomized to either supervised twice-weekly resistance exercise training and 150 minutes per week of aerobic exercise (N=61) or a usual care (N=60) group. Dual energy X-ray absorptiometry (DXA) scans were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 39 publications
3
79
0
3
Order By: Relevance
“…43 Another randomized trial compared a combined aerobic and resistance exercise program versus usual care among 121 breast cancer survivors taking aromatase inhibitors and reported significant increases in lean body mass and decreases in body fat over 12 months. 44 Finally, in an exploratory study, 20 subjects were randomized to either a 16 week aerobic and resistance training program versus delayed control. Exercise participants experienced significant improvements in lean body mass, percent body fat, and fat mass.…”
Section: Intervention Studies On Body Composition Among Breast Cancermentioning
confidence: 99%
“…43 Another randomized trial compared a combined aerobic and resistance exercise program versus usual care among 121 breast cancer survivors taking aromatase inhibitors and reported significant increases in lean body mass and decreases in body fat over 12 months. 44 Finally, in an exploratory study, 20 subjects were randomized to either a 16 week aerobic and resistance training program versus delayed control. Exercise participants experienced significant improvements in lean body mass, percent body fat, and fat mass.…”
Section: Intervention Studies On Body Composition Among Breast Cancermentioning
confidence: 99%
“…Moreover the athlete's blood, independently tested at the laboratory of a national hospital for a panel of biochemical indicators (including transferrin, ferritin, luteinizing hormone, follicle stimulating hormone, delta‐4‐androstenedione, 17‐alfa hydroxyl progesterone, dehydroepiandrosterone, and 17‐betaestradiol), resulted normal, and a physical examination, including the calculation of BMI (22.7), body surface area (BSA) (1.66 m 2 , method Du Bois ) and seven skinfold measurements according to Jackson Pollock Formula (fat mass: 16.22%) did not reveal any effects of letrozole or other AIs capable of decreasing fat body mass or giving muscle definition. According to previous studies, AI consumption is responsible for a significant increase in lean mass and a decrease of fat mass in treated postmenopausal women with respect to controls …”
Section: Discussionmentioning
confidence: 91%
“…We conducted a randomized exercise trial in 121 breast cancer survivors who were randomized to either an exercise intervention or usual care. We previously reported that exercise led to a significant 30% improvement in AI‐associated arthralgias and improved body composition among previously inactive breast cancer survivors . We also reported that long‐term exercise adherence was feasible among women with breast cancer who were experiencing pain because of AI‐associated arthralgia .…”
Section: Introductionmentioning
confidence: 91%
“…17,18 We also reported that longterm exercise adherence was feasible among women with breast cancer who were experiencing pain because of AI-associated arthralgia. 18 To our knowledge, the impact of exercise on endocrine-related QOL among women who are receiving an AI for the treatment of early stage breast cancer and are experiencing arthralgia have not been reported to date. We hypothesized that exercise would have a positive effect on endocrinerelated QOL among these women.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation